Initial training for teachers of physical education to face reality of a school inclusion - Victor Julierme Santos da Conceição; Hugo Norberto krug (Universidade Federal de Santa Maria (UFSM), 2009)
This study, had as main objective to accomplish one it analyzes about the contribution of the critical-reflexive teaching in the physical education teachers' initial formation, as the inclusion, in common class, of students with special educational needs. So that if it could approach the intentions foreseen for this investigation, it was used the beginnings of the participant research as methodological source. Being the subjects constituted by five academic of the course of Degree in physical education, in situation of teaching practice, of Santa Maria's Federal University. Semi-structured interview, participant observation and documental analysis, they were the used instruments and registered in field diary in a period of a school semester of the year of 2005. The data send the conclusions for the trainees' needs to observe the educational space, based in the critical reflection, for if they involve in the decisions that are part of this context. Facing this movement as an understanding of the world to your turn, contributing to understand the current process of the students' inclusion with special educational needs. Lifting the problematic principal that refer the formative needs of the subject.